PERCEPATAN PENINGKATAN PRODUKSI PADI SAWAH MELALUI UMUR BIBIT - Misran Misran (UIR Press, 2013)
Seedling age on the transplanting system is one of the factors that affect productivity of rice crop. This research attempted to determine the effect of seedling age of rice production for obtain the optimal yield. The experiment was conducted on farmer’s rice field in Lubuk Minturun Sungai Lareh village, Koto Tangah district, Padang city, West Sumatra Province, from September 2009 to January 2010. Randomized Block Design (RBD) with four replications and six treatments was used. The treatments were seedling age, namely A (10 days after sowing), B (15 days after sowing), C (20 days after sowing), D (25 days after sowing), E (30 days after sowing) , and F (35 days after sowing). The seedlings used were Batang Lembang variety which was planted on 4 x 5 m plots with a spacing of 25 x 25 cm and three seedlings per hill. Fertilizers used are 150 kg Urea, 100 kg SP36, and 75 kg/ha KCl and were given at 7, 28, and 45 days after planting (DAP ), while the SP36 was given entirely at DAP 7 together with giving Urea and KCl. The parameter measured included plant height, maximum number of tiller/hill, number of productive tiller/hill, yield components, and yield. The results showed that the seedling age affected significantly (P < 0.05) plant height, maximum number of tillers, yield components and yield. The treatment of 20 days on after sowing showed the highest yield components and grain yield, while the treatment seedlings of 35 days after sowing was lowest grain yield. The results suggest that the optimal yield of rice in transplanting system will be obtained by using the 20-day old seedlings.